Multiaxial ultra low cycle fatigue in welded high strength steel structural components. (February 2019) - de Castro e Sousa, Albano; Nussbaumer, Alain
Abstract: Extreme events often subject regions of structural steel components to large inelastic strains. In conditions such as earthquakes, exceptional winds gusts or tides the loading scenario is cyclical, variable amplitude and frequently multiaxial in nature, and failure of a component can often be atributed to a phenomenon known as ultra low cycle fatigue (ULCF). Failure in this regime is reached typically within ten to twenty cycles as a consequence of the sizable amplitudes to which the material is strained. This paper focuses on a methodology to assess welded high strength steel component resistance to ULCF using a local approach. More than sixty tube to plate joints experiments on welded high strength steel (S770QL) are presented. These components were submitted to high cyclic bending, pure torsional and combined proportional bending and torsional loadings and variable amplitude loading. Weld profile and strain measurements (up to 10% amplitude) at the weld toe were performed using digital image correlation (DIC). These original results using DIC measurements suggest that using a local equivalent strain metric at the weld toe provides a consistent resistance model in strain-life terms. Mesh requirements in line with local approaches to fatigue are proposed for finite element simulation assessment of ULCF strength in multiaxial conditions for high strength steel. Highlights: Over sixty experiments of welded high strength steel joints in multiaxial ULCF Digital image correlation results for strain amplitudes of up to 10% Design oriented evaluation procedure for ULCF